2016
DOI: 10.5296/jas.v4i4.9482
|View full text |Cite
|
Sign up to set email alerts
|

Non-Timber Forest Products Trade and Community Livelihoods around Mabira Central Forest Reserve, Uganda

Abstract: This paper generates data on the diversity and value of non-timber forest products (NTFP) traded in markets adjacent to Mabira Central forest reserve. The objective of the study was to evaluate the contribution of NTFP trade to the livelihoods of traders' households. Quarterly market surveys and field observations were conducted in eleven markets in 2014. All NTFP ISSN 2166-0379 2016 www.macrothink.org/jas 2 traders were interviewed using semi structured questionnaires. Simple profitability method was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…The sale of environmental products offers an important means for rural households to generate cash-income in low-income countries (S. Shackleton, Campbell, Lotz-Sisitka, & C. Shackleton, 2008;Shackleton & Pandey, 2014;Tugume et al, 2016). In particular, products such as fuel wood, construction materials, medicines, and food-stuff including wild fruits, vegetables and bush-meat contribute significantly to rural households' economic wellbeing (Mamo, Sjaastad, & Vedeld, 2007;Saha & Sundriyal, 2012;Langat, Maranga, Aboud, & Cheboiwo, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sale of environmental products offers an important means for rural households to generate cash-income in low-income countries (S. Shackleton, Campbell, Lotz-Sisitka, & C. Shackleton, 2008;Shackleton & Pandey, 2014;Tugume et al, 2016). In particular, products such as fuel wood, construction materials, medicines, and food-stuff including wild fruits, vegetables and bush-meat contribute significantly to rural households' economic wellbeing (Mamo, Sjaastad, & Vedeld, 2007;Saha & Sundriyal, 2012;Langat, Maranga, Aboud, & Cheboiwo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The trade of environmental products can be either as supplementary income to other livelihood activities, or as primary means of cash generation (Mahapatra & Tewari, 2005). This trade appears to be growing worldwide, due to greater need for cash income as households become more integrated into the market economy; and due to economic hardship and increased vulnerability as a consequence of unemployment and poor agricultural production (Shackleton, Delang, & Angelsen, 2011;Steele, Shackleton, Uma Shaanker, Ganeshaiah, & Radloff, 2015;Tugume et al, 2016). In recent years, there has been growing interest in the contribution of environmental resources especially non-timber forest products (NTFPs) to livelihoods, development, and poverty alleviation in rural areas (Babulo et al, 2009;Kar & Jacobson, 2012;Hogarth, Belcher, Campbell, & Stacey, 2013;Suleiman, Wasonga, Mbau, Suleiman, & Elhadi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 85% of Uganda's population relies directly on natural resources for livelihoods (Final Draft NEMP 2014), and fuelwood contributes more than 96% of energy for cooking (USAID 2015). In addition to fuelwood, non-timber forest products are used for charcoal, medicinal herbs, food and crafts (Tugume et al 2016). If people in the study area can continue to access the CFRs as part of the offset (albeit with restrictions), they may benefit considerably from their restoration and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…If people in the study area can continue to access the CFRs as part of the offset (albeit with restrictions), they may benefit considerably from their restoration and maintenance. Tugume et al (2016) found that people around the Mabira CRF (within the Kalagala Offset catchment) recognised the non-financial benefits of forests, and in particular, their importance in rainfall formation.…”
Section: Discussionmentioning
confidence: 99%
“…The most predominant products in our study were valueadded products from the fruit. Some studies have found that profits from harvest of wild plant products can be a highly volatile proposition (Arnold and Pérez 1998), but others demonstrate that this challenging industry has the potential to give good profit margins (Belcher and Schreckenberg 2007;Tugume et al 2016). Perhaps, the most assuring observation on local harvesters is not the promise of income, but that wild plant products provide a valuable safety net of food and basic necessities for economically disadvantaged families (Shackleton and Shackleton 2004).…”
Section: Discussionmentioning
confidence: 99%